CYTOLOGICAL, ULTRASOUND AND BIOCHEMICAL CORRELATION IN HASHIMOTO’S THYROIDITIS, FARIDABAD, INDIA: A RETROSPECTIVE CROSS-SECTIONAL ANALYSIS. - Aggarwal, Malika Mehta; Aggarwal, Dhruv; Aggarwal, Pearl (Student’s Journal of Health Research Africa, 2024)
Background Hashimoto’s thyroiditis, an autoimmune disorder that impairs thyroid hormone production via antibody-mediated destruction of thyroid cells, affects women more frequently and presents symptoms like weight gain and fatigue. This study investigates the correlation between cytomorphological, biochemical, and radiological findings in diagnosing this condition, utilizing Fine Needle Aspiration Cytology (FNAC) as a key diagnostic tool. Materials and methods A retrospective analysis of cytological, radiological, and biochemical parameters was done for 84 patients who underwent FNAC for Hashimoto’s Thyroiditis. The blood concentration of thyroid hormones was evaluated by the Thyroid Function Test (TFT). Thyroid ultrasound was done using a high-frequency linear ultrasound transducer. Results This study found Hashimoto’s thyroiditis more common in females (95%) and primarily in those aged 20-40 years. Biochemical hypothyroidism (Thyroid function test) was observed in 50% of the selected patients, euthyroidism was observed in about 43% of the patients, and hyperthyroidism was observed in 7 % of the patients. Cytological findings showed mild, moderate, and dense lymphocytic infiltration in 32.15%, 41.66%, and 26.20% of patients across Grades I, II, and III, respectively. Moreover, 51% of the patients were affected with diffuse thyroiditis, 35% of the patients were affected with goiter, 8% of the patients were affected with thyroid nodules, and the remaining 6% of the patients were seen to be normal in the ultrasound findings. Conclusion Hashimoto’s Thyroiditis is more prevalent in females, with elevated biochemical results linked to higher FNAC grades. Early detection of diffuse thyroiditis using ultrasound assists in predicting the disease before clinical signs appear. Integrating biochemical, cytology, and ultrasound findings can identify subclinical hypothyroidism. Recommendation For early detection and precise staging of Hashimoto’s Thyroiditis, integrating cytomorphological, biochemical, and radiological diagnostics is advised. Future research should aim at refining treatment strategies based on these findings.